Radioguided Adrenal Surgery: Access in Complex Situations: Technical Notes. Issue 39 (September 2015) - Deus, Javier; Millera, Alfonso; Andrés, Alejandro; Prats, Enrique; Gil, Ismael; Suarez, Manuel; Salcini, José L.; Lahoz, Manuel
Abstract : Abstract: The laparoscopic adrenalectomy is considered as the procedure of choice for the treatment of adrenal hyperplasia and tumor lesions. However, some special situations may limit the use of this method due to the difficulty to locate the gland and perform the lesion excision. We analyze 2 patients of a left adrenal tumor, explaining how they have overcome the difficulties in both situations. The first case was a patient with a history of intra-abdominal surgery and the other patient suffered from severe obesity. We performed with the use of the gamma probe, and the 2 cases, was of great help to access and glandular localization. The help of gamma probe test was achieved in the surgical bed, that removal was complete. The use of the portable gamma probe facilitated the access to the left adrenal gland as well as conducting the glandular excision without delay, despite the difficulties due to the intra abdominal surgery caused by the previous surgery, and in the case of severe obesity.